Implementation of Patient Safety in Hospitals Related to Patient Satisfaction in 2023 - Ningrum, Apriliya Tiyas; Putri, Imram Radne Rimba; Sarwadhamana, Raden Jaka (Media Keperawatan Indonesia, 2024)
The incidence of non-injury incidents at Panembahan Senopati Hospital, Bantul is still the highest case every year, this is still several non-injury incident cases of 45.5% in 2022, this case is because there are still nurses or health workers who have not fully implemented patient safety properly. Patient safety in hospitals is the main foundation for creating safe, comfortable services for the creation of healing for patients, which we hope will affect patient satisfaction. This study aims to determine the relationship between the implementation of patient safety and patient satisfaction in the inpatient ward of Panembahan Senopati Hospital, Bantul. This research is a quantitative study with a cross-sectional design. Sampling using accidental sampling technique with 150 inpatient respondents. The measuring tool used is a questionnaire application of patient safety and patient satisfaction. The statistical test used is the Kendall Tau test. The results of the study show that there is a relationship between the application of patient safety on patient satisfaction in the inpatient room of Panembahan Senopati Bantul Hospital with a close relationship in the sufficient category indicated by a coefficient (r) of 0.345 with a p-value: 0.000 (<0.05). The conclusion in this study is that there is an application relationship between patient safety on patient satisfaction in the inpatient room of Panembahan Senopati Hospital, Bantul.